ANALISIS PENGARUH CAR, FDR, DAN NPF TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA - Azizah, Siti Nur (Jurnal Riset Keuangan dan Akuntansi, 2024)
The purpose of this study is to determine the effect of capital adequacy ratio, financing to deposit ratio, and non-performing financing. Sample selection in this study was carried out by purposive sampling. Based on the criteria, 54 financial statements of Islamic commercial banks were sampled. The data analysis techniques used in this study are descriptive statistical tests, classical assumption tests, multiple linear regression tests, and model feasibility tests. The results of the analysis show that the capital adequacy ratio has a positive effect on profitability, while the financing to deposit ratio does not affect profitability, and then non-performing financing has a negative effect on profitability. Keywords: Profitability, capital adequacy ratio, financing to deposit ratio, and non-performing financing.